Can multicultural human resources management problems be solved by an organisational culture? - Karjalainen, Helena (Management international / Gestiòn Internacional / International Management, 2010)
During recent decades, globalisation has affected and changed functions of enterprises, firms must adapt their strategies to global business and to international human resources management. A new challenge seems to be imposed to international managers and to international HRM: how to create cooperation between employees representing different cultural backgrounds and how to find a common identity in multicultural teams? Our article, based on a case study, inter-site cases, examines five different multicultural work groups. Results reveal how cooperation can be created and managed with the HRM practices and tools: recruitment, intercultural management, mediation and organisational culture.